(Development of Screw press design for coconut milk extraction) - Susanto, Eko; Yang Setiawan, Yang; Wuri Handono, Sri; Tojib, Mochtar; Timur Antara, Ngakan (Warta Industri Hasil Pertanian, 2003)
Research and developmen of screw press construction has been conducted to imporove yield of coconut milk .the equitment was used to improve extration effcieny compared with other methodeswere used to compare traditional method ,hydraulic press and screw screw that the optimum condition of equipment is 167 pm and its ower 1 HP its produced coconut milk about 68.24 percent (w/w) and oil content in the waste was 22.12 percent (db)